Cochran's German review grammar - Cochran, Emory Ellsworth; Conant, Jonathan B., 1941- (Englewood Cliffs, N.J. : Prentice Hall, 1991)
A reference and review grammar of German for second year students.
Includes index.
Keywords: German language -- Grammar; German language -- Grammar